Empires and Communities in the Post-Roman and Islamic World, c. 400 - 1000 CE - Kramer, Rutger; Pohl, Walter (2021)
This book deals with the ways in which empires affect smaller communities - for instance, ethnic groups, religious communities, local or peripheral populations. It addresses Byzantinium, the early Islamic World and the West in the 5th to 10th centuries CE, a period with a particular dynamic of imperial formation and decline in Europe and the Mediterranean.